Determinants of Compliance Among Chronic Kidney Disease Patients Undergoing Hemodialysis at RSUD ODSK, North Sulawesi - Irene R. Rondonuwu; Nova H. Kapantow; Suryadi N. N. Tatura (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Chronic Kidney Disease (CKD) is a major chronic health issue that requires long-term therapy, one of which is hemodialysis. The success of hemodialysis therapy is highly influenced by patient adherence. However, the adherence rate to scheduled hemodialysis at ODSK Provincial General Hospital, North Sulawesi, is only 71.67%, which is still below the National Quality Indicator standard of 100%. This study aimed to analyze the factors influencing adherence among CKD patients undergoing hemodialysis at ODSK Provincial General Hospital in North Sulawesi. A quantitative approach with a cross-sectional design was employed. The sample consisted of 78 CKD patients who routinely underwent hemodialysis, selected using total sampling. Data were collected through a structured questionnaire. Chi-square tests and logistic regression analyses were conducted to assess the relationships between variables. The results revealed significant associations between adherence and several factors, including education level (p=0.009), duration of hemodialysis (p=0.004), knowledge (p=0.013), nurse support (p=0.006), and family support (p=0.006). The most influential factors were family support and patient knowledge, with family support emerging as the strongest predictor of adherence among CKD patients undergoing hemodialysis. Efforts to improve adherence should focus on patient education, strengthening the role of nurses and hospital services, and actively involving family members in the patient care process.